The influence of photon excitation and proton irradiation on the luminescence properties of yttria stabilized zirconia doped with praseodymium ions - Soares, M. R. N.
Lanthanide doped zirconia based materials are promising phosphors for lighting applications. Transparent yttria stabilized zirconia fibres, in situ doped with Pr3+ ions, were grown by the laser floating zone method. The single crystalline doped fibres were found to be homogeneous in composition and provide an intense red luminescence at room temperature. The stability of this luminescence due to transitions between the 1D2 → 3H4 multiplets of the Pr3+ ions (intra-4f2 configuration) was studied by photo- and iono-luminescence. The evolution of the red integrated photoluminescence intensity with temperature indicates that the overall luminescence decreases to ca. 40% of the initial intensity at 14 K when heated to room temperature (RT). RT analysis of the iono-luminescence dependence on irradiation fluence reveals a decrease of the intensity (to slightly more than ∼60% of the initial intensity after 25 min of proton irradiation exposure). Nevertheless the luminescence intensity saturates at non-zero values for higher irradiation fluences revealing good potential for the use of this material in radiation environments.